(untitled) (Journal of Multidisciplinary Sciences and Innovations, 2025)
Vocabulary development is crucial in English for Specific Purposes (ESP), where learners must master terminology specific to a profession or academic discipline. Traditional vocabulary instruction, often centered on memorization, may fail to ensure long-term retention or meaningful use. This article examines the benefits of a Task-Based Learning (TBL) approach to teaching vocabulary in ESP contexts. It outlines a structured methodology for integrating TBL in the ESP classroom and discusses outcomes related to learner engagement, vocabulary acquisition, and communicative competence.